PROSPECTS FOR BUILDING LABOR POTENTIAL IN THE CONTEXT OF EUROPEAN INTEGRATION PROCESSES - BERESTETSKA, Olena; BEZZUBKA, Vasyl (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article identifies the prospects for increasing labor potential in the context of European integration processes. Literary sources are analyzed in order to determine the essence of the country's labor resources. The current state of the country's labor resources and prospects for increasing the labor potential are highlighted. The key aspects of cooperation between Ukraine and the European Union are identified. The problems of increasing labor potential and development of labor resources in the context of the armed aggression of the Russian Federation against Ukraine are investigated. The author emphasizes that increased migration activity, rising unemployment and loss of income for a large part of the population have led to a deepening of inequality in income distribution. In addition, it is noted that increased competition in the labor market and a shortage of human resources in the context of war impede the development of the country's labor potential. Effective ways to increase the labor potential in Ukraine during the war and in the context of the development of European integration processes are investigated. It was determined that the top priorities are the implementation of financial support programs for enterprises and the population, raising the minimum wage, developing social security, developing measures to improve the psychological state of the population, and implementing European standards of equal rights and opportunities for all segments of the population. It is noted that the current strategy for the development of human capital in Ukraine involves the attraction of foreign labor and support from the European Union and partners. The author analyzes the key programs and initiatives of the European Union aimed at developing the labor potential of Ukraine. It is determined that active cooperation with the European Union in the field of scientific and technological programs contributes to the formation of an innovative environment, but will require reforms in the field of labor resources, and it is important to start the necessary changes in the short term.
Keywords: labor potential; labor resources; social capital; migration; unemployment; European integration